Implementation of Digital Governance Policy of Earthquake and Tsunami Information System in Cilegon City, Banten Province - Maulana, Akhmad Taufan; ., Andriansyah; Muksin, Nani Nurani; Satispi, Evi; Samudra, Azhari Aziz; Oktariani, Andina (Journal of Ecohumanism, 2025)
To facilitate bureaucratic reform, state administration began to change the bureaucratic work pattern, which was originally oriented towards service to bureaucrats, changing to an orientation towards service to the community. The paradigm of reinventing government and good governance not only triggers the emergence of the concept of autonomy, participation, efficiency and public service, but also policy networks. A society that lives in a healthy public administration that can achieve public interests will form a deliberative society that lives in deliberative public policies. This study aims to describe how the Implementation of Digital Governance Policy for Earthquake and Tsunami Information Systems in Cilegon City, Banten Province. Qualitative descriptive research method with literature study to collect data and information. The results of the study indicate that the implementation of digital governance policy for earthquake and tsunami information systems in Cilegon City generically follows the Broadcasting/Wider-Dissemination Model which provides valuable information to the general public and determines the priority of future actions.